Pengaruh Suhu dan Tekanan terhadap Hasil Penggorengan Keripik Belimbing (Averrhoa carambola L.) Menggunakan Vacuum Frying - Asmara, Sandi; Rahmawati, Winda; Kuncoro, Sapto; Amanullah, Deo Arif (abe.fp.unila.ac.id, 2024)
Fruit chips are healthy snacks because of their high fiber content. One of the fruit commodities being developed is the starfruit (Averrhoa carambola L.) commodity. Starfruit is a fruit that is widely processed into other processed foods, because the fruit is easily damaged and has a relatively short shelf life of 3 to 4 days. Fruit chips are more resistant to storage than fresh fruit because their water content is low and physiological processes no longer occur. The equipment used to make fruit chips is a vacuum fryer which has the advantage of frying fruit into chips. The purpose of this study was to analyze the effect of frying temperature and pressure on product quality in the manufacture of starfruit chips using vacuum frying and to determine the optimal temperature and pressure for frying starfruit chips using vacuum frying. The research method used was an experimental design in the form of a factorial Completely Randomized Design (CRD). Experimental factors in this study used two factors, temperature (T), namely temperature 75°C, 80°C, 85°C and pressure (P) during the frying process namely -68 cmHg, -70 cmHg and -72 cmHg, with as many repetitions as 3 times to produce 27 experimental units. The parameters observed in this study were the analysis of material shrinkage (yield), water content, organoleptic tests, and analysis of storage of starfruit chips. It can be concluded that the optimal choice of temperature and pressure in the operation of a vacuum frying equipment for making starfruit chips is 80°C with a low frying pressure of -72 cmHg. The quality of starfruit chips with a temperature of 80°C and a frying pressure of -72 cmHg was included in the best product category in this study based on overall acceptance which had a material yield value of 13.09%, a moisture content of 4.64%, and a color organoleptic test score of 4. 13 (yellow), aroma 3.67 (starfruit aroma is rather strong), taste 4.40 (slightly sweet), crispness 4.00 (crunchy). Keywords: Chips, Starfruit, Vacuum Frying